Gene expression cluster differences and molecular correlation with the STING pathway in orbital MALT lymphoma and orbital IgG4-related eye disease - Mizuki Tagami; Keishiro Isayama; Mizuho Nishio; Atsuko Yoshikawa; Norihiko Misawa; Atsushi Sakai; Yusuke Haruna; Mami Tomita; Yoichi Mizukami; Atsushi Azumi; Shigeru Honda (Discover Oncology)
Abstract Purpose Mucosa-associated lymphoid tissue (MALT) lymphoma in the orbital region and IgG4-related ophthalmic disease (IgG4-ROD) account for the majority of mass lesions in the orbital region. These diseases may show similar shadows on radiologic images, and many cases are difficult to differentiate clinically. Using histology, we investigated the gene expression clusters (RNA-seq) and molecular differences responsible for these two diseases. Design Retrospective cohort study. Subjects Patients diagnosed with orbital MALT and IgG4-ROD who underwent surgical treatment at Osaka Metropolitan University or Kobe Kaisei Hospital, Japan, were included in the study. Methods Fresh tissues extracted from 20 cases of MALT lymphoma and IgG4-ROD histopathologically diagnosed were subjected to next-generation sequencing analysis, and a sequence library was generated. Next-generation sequencing analysis was performed to compare gene expression between the two groups, and principal component and cluster hierarchy analyses were performed. Genes exhibiting significant changes in expression were examined individually after pathway analysis; immunohistochemical staining was performed to determine the intensity and staining morphology of components of significantly altered pathways. Main outcome measures Gene cluster differences between orbital MALT lymphoma and IgG4-ROD. Results In principal component analysis, orbital MALT lymphoma and IgG4-ROD clustered in component 2. Clear cluster differences were observed, except for one case that appeared to be IgG4-producing MALT lymphoma. This apparent case of IgG4-producing MALT lymphoma clustered just between the IgG4-ROD and MALT lymphoma clusters. Analysis of upregulated genes between IgG4-ROD and MALT lymphoma identified 582 candidate genes (P < 0.01). Pathway analysis of MALT lymphoma suggested that the STING pathway was activated. Downstream pathway analysis identified eight significant gene expression changes (P < 0.05). STING immunohistochemical analysis indicated a quantitative difference in staining pattern between IgG4-ROD and MALT lymphoma (P < 0.01). STING-positive staining within cells was significantly greater in MALT than the Golgi complex near the nucleus. Conclusions Orbital MALT lymphoma and IgG4-ROD can be differentiated by two gene expression clusters. The STING pathway may play a more important role in orbital MALT lymphoma than orbital IgG4-ROD.